2018
DOI: 10.1051/matecconf/201821119001
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of flow phenomena in hydraulic throttle valves of plastics

Abstract: Using elements made of plastics in hydraulic drives and controls encounters problems, for example related to strength. However, the advantage of solutions with plastics manifests itself, among others in possibility of shaping hydraulic elements in accordance with the assumed requirements. The use of additive manufacturing techniques allows us to make plastic parts with shapes that are unattainable for steel parts. The authors have attempted to determine the influence of the shape of the closing element on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Less strength and greater elasticity leads to greater deformations. This was also confirmed in the case of such hydraulic elements made of plastics like gerotor pumps [8][9][10] or valves [11].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Less strength and greater elasticity leads to greater deformations. This was also confirmed in the case of such hydraulic elements made of plastics like gerotor pumps [8][9][10] or valves [11].…”
Section: Introductionmentioning
confidence: 54%
“…Figure 5b shows that the laser sensors are placed in a special holder (11). The holder is attached to the rigid frame of the test stand (1) and has no direct contact with the tested cylinder, the structure of which deforms and, as a result, moves relative to the frame.…”
Section: Research Stand and Methods Of Testingmentioning
confidence: 99%
“…The injection molded pressure relief valve is further documented by Marciniak et al [17], showing successful computational fluid dynamics (CFD, finite element method (FEM), and experimental test results as well as a comparison to an industrial metal relief valve. Another paper from the same research group investigates the flow phenomena in a throttling valve 3D printed from poly(methyl methacrylate) (PMMA) at flow rates up to 10 L/min experimentally and numerically using CFD [18]. They note that some downfalls of 3D-printed plastic include lower strength and larger deformation, and materials such as polylactic acid (PLA) do not have sufficient hardness to form sharp edges.…”
Section: P Cmentioning
confidence: 99%
“…Shi et al [9] experimented with suppressing the cavitation of throttle valves in water hydraulics. Banaś et al [10] studied a cone throttle valve by means of visualisation. In studying a direct‐acting hydraulic relief valve, Yang et al [11] found that the arrow‐shaped compensation structure, an appropriate valve core cone angle, and the secondary valve port can effectively improve the valve performance.…”
Section: Introductionmentioning
confidence: 99%